Principios éticos de la bioética y el bioderecho europeos: autonomía, dignidad, integridad y vulnerabilidad (2020)
Toe main goal of this article is to discuss the episternological and practical features of the basic ethical principies in European bioethics and biolaw as a result of a relevant project supported by the European Commission between 1995 and 1998. That project was based on cooperation between 22 partners corning frorn most EU countries. Its aim was to identify the ethical principies relating to autonomy, dignity, integrity and vulnerability as four important ideas or values for European bioethics and biolaw. In this paper it will be showed how the author reaches the conclusion that the basic ethical principies cannot be understood as universal, everlasting ideas or transcendental truths but they rather function as "reflective guidelines", and important traditional values in European culture.